PARENTS ASSISTANCE PROGRAM FOR THE DEVELOPMENT OF CHILD CREATIVITY LEARNING FROM HOME USING USED GOODS THROUGH THE GOOGLE MEET APPLICATION - Maria Assumpta Juniarti Harry Susanti; Annisa Us Sholihah; Wahyuni Wahyuni; Nurwiddayu Asra; Ajeng Priendarningtyas (UNIVERSITAS PAKUAN, 2021)
This study aims to reveal the actual situation about; (1) The effectiveness of parents in developing children's learning from home, (2) What kind of guidance is given to parents of students to increase the effectiveness of developing children's creativity learning from home. The research method used is descriptive method with a qualitative approach. The number of respondents used as the unit of analysis is as many as 10 respondents, namely parents of students in PAUD and TK Hobi Hobi. The results showed that; (1) At present, parents of students do not understand how the phase of child development is in assisting children to learn from home, then, some parents are overprotective so that the development of children's independence does not develop optimally. (2) The guidance provided is parenting, and fostering children's independence.